Family businesses listed on the Johannesburg Stock Exchange: An introduction and research agenda - Suzette Viviers; Elmarie Venter (South African Journal of Economic and Management Sciences)
Background: Despite the significant socio-economic contribution of family businesses (FBs) in South Africa, scant research has been conducted on listed FBs, mainly because of the lack of a comprehensive sample frame and appropriate research agenda.